2008
DOI: 10.1016/j.jad.2007.05.031
|View full text |Cite
|
Sign up to set email alerts
|

No association between a TPH2 promoter polymorphism and mood disorders or monoamine turnover

Abstract: Background-Tryptophan hydroxylase (TPH) is the rate-limiting enzyme in serotonin synthesis. TPH2 is a recently discovered isoform that is expressed predominantly in serotonin neurons. Associations are reported of TPH2 polymorphisms with MDD, bipolar disorder and suicidal behavior. This study examines a single nucleotide polymorphism in the putative promoter region of the TPH2 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
1
14
1
Order By: Relevance
“…Furthermore, we could not demonstrate any association between haplotype variants of the TPH2 gene and BSI depression, BSI anxiety, BFI neuroticism, or IVE impulsiveness scores. This is in agreement with recent studies which failed to find any association between the TPH2 gene and depression/suicidal behavior (Mann et al, 2008;Must et al, 2007;Zill et al, 2007b;De Luca et al, 2006;Lopez et al, 2007b), but in contrast to earlier findings reporting such an involvement (Zill et al, 2004a, b;Zhou et al, 2005;Van Den Bogaert et al, 2006;Haghighi et al, 2008;Lopez et al, 2007a;Ke et al, 2006). Therefore, the interpretation we favor is that the variations in the TPH2 gene might be linked to an endophenotype influencing risktaking behavior that could be an additive or in some cases a vulnerability factor, for psychiatric disorders, for example, affective disorders or disturbed mood in impulse control or substance misuse disorders.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, we could not demonstrate any association between haplotype variants of the TPH2 gene and BSI depression, BSI anxiety, BFI neuroticism, or IVE impulsiveness scores. This is in agreement with recent studies which failed to find any association between the TPH2 gene and depression/suicidal behavior (Mann et al, 2008;Must et al, 2007;Zill et al, 2007b;De Luca et al, 2006;Lopez et al, 2007b), but in contrast to earlier findings reporting such an involvement (Zill et al, 2004a, b;Zhou et al, 2005;Van Den Bogaert et al, 2006;Haghighi et al, 2008;Lopez et al, 2007a;Ke et al, 2006). Therefore, the interpretation we favor is that the variations in the TPH2 gene might be linked to an endophenotype influencing risktaking behavior that could be an additive or in some cases a vulnerability factor, for psychiatric disorders, for example, affective disorders or disturbed mood in impulse control or substance misuse disorders.…”
Section: Discussionsupporting
confidence: 94%
“…Although earlier studies reported significant associations between several TPH2 SNPs and both depression and suicidal behavior (Haghighi et al, 2008;Ke et al, 2006;Lopez de Lara et al, 2007;Van Den Bogaert et al, 2006;Zhou et al, 2005;Zill et al, 2004a, b) more recent studies failed to confirm these findings (De Luca et al, 2006;Mann et al, 2008;Zill et al, 2007). Among functionally characterized TPH2 polymorphisms only a few (including G1463A) result in a clear reduction in enzymatic activity, whereas other polymorphisms have only a minor effect on TPH2 activity (McKinney et al, 2009).…”
Section: Human Tph2 Polymorphismsmentioning
confidence: 99%
“…Since the discovery of the tryptophan hydroxylase 2 (TPH2) isoenzyme (Walther et al, 2003)Fthe rate-limiting enzyme of 5-HT synthesis in the brainFTPH2 polymorphisms in humans have been associated with anxiety traits, depressive disorders, and suicidality (Gutknecht et al, 2007;Reuter et al, 2007;Van Den Bogaert et al, 2006;Zhang et al, 2005;Zill et al, 2004a, b) yet these results have not been supported by other studies (De Luca et al, 2006;Garriock et al, 2005;Juhasz et al, 2010;Mann et al, 2008;Middeldorp et al, 2010). These discrepancies might be partially attributed to the fact that different SNPs in the TPH2 gene were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…[104][105][106] There are almost no reports of functional consequences of TPH2 gene variation. One recent study in healthy volunteers found evidence of a frequent functional cis-acting polymorphism in the TPH2 gene that affected mRNA expression.…”
Section: Tph Genes and Suicidal Behaviormentioning
confidence: 99%